2009
DOI: 10.1590/s1807-59322009000800005
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication: Initial Treatments Used by Patients Seen in an Ophthalmologic Emergency Room

Abstract: OJECTIVEThis study seeks to identify practices of self-medication in the treatment of ocular emergencies. We examine patients’ use of both homemade preparations and manufactured products before seeking specialized care.MATERIALS AND METHODSWe conducted a cross-sectional analytic survey of consecutive patients seen in the ophthalmology emergency room of a teaching hospital.RESULTSThe sample included 561 subjects, 51.3% males and 48.7% females, with a mean age of 39.8 years. Prior to seeking emergency care, 40.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 15 publications
3
43
2
4
Order By: Relevance
“…In a study by Regina et al , it was found that almost 40.5% people self-medicate before seeking specialised care for ocular emergencies 1. The study also noted that this practice of self-medication is independent of one's educational level 1. Similar findings have been reported by Mouhari et al in dermatology, too.…”
Section: Global Health Problem Analysissupporting
confidence: 73%
See 1 more Smart Citation
“…In a study by Regina et al , it was found that almost 40.5% people self-medicate before seeking specialised care for ocular emergencies 1. The study also noted that this practice of self-medication is independent of one's educational level 1. Similar findings have been reported by Mouhari et al in dermatology, too.…”
Section: Global Health Problem Analysissupporting
confidence: 73%
“…In yet other populations, tongue therapy (or using one's tongue to clean the patient's eye) has also been practised as a curative measure for a variety of ocular ailments. In a study by Regina et al , it was found that almost 40.5% people self-medicate before seeking specialised care for ocular emergencies 1. The study also noted that this practice of self-medication is independent of one's educational level 1.…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…The study design has the strength of being population-based; however, care should be taken in applying the results as there are socio-cultural variations across the globe. 24 The prevalence of ocular self-medication among inhabitants of the Cape Coast is comparable to that in Ibadan, Nigeria 25 and some three towns of North West Ethiopia 26 indicating that practice is prevalent in comparable proportions across the continent. This phenomenon is reported as the first option approach among some rural African popuation.…”
Section: Discussionmentioning
confidence: 90%
“…In a study performed at a university hospital emergency (24) , it was found that 29.4% of the patients use homemade products as the first management for the treatment of ocular diseases. Information about what people know and do regarding ocular problems is an important data for prevention and educational health programs (25) .…”
Section: Post-visit At Ophthalmology Emergency Service: Frequency Andmentioning
confidence: 99%